Investigation of Factors That May Constrain Participation of Sportive and Non-Sportive Recreational Activities Among University Students - Nurullah Emir Ekinci; Aslan Kalkavan; Ümit Doğan Üstün; Bolat Gündüz (ümit doğan üstün, 2014)
The purpose of this study was to analyze, which recreational sport or non- sport such as cultural/ art activities that university students prefer in their leisure time and underlying reasons that constrains participating in these activities with regard to different variables. Randomly chosen 339 students from The Faculty of Arts and Faculty of Sciences and Engineering at University of Dumlupiınar volunteered for the study. In this research as a data collection tool "Leisure Constraint Scale" was used. During the evaluation of the data in addition to descriptive statistical methods such as Percentage (%) and frequency (f) Independent Samples t-test and One way Anova were used. As a result it was found that 19.2% participants choose recreational sport activities in their leisure time. In addition, significant differences have emerged between participants' gender and constrains to leisure in "lack of information", "lack of friends" and "time" sub-dimensions, between age and barriers to leisure in "time" sub-dimension, and between average monthly income levels and constrains to leisure in "individual psychology" and "facilities / services" sub dimensions (p <0.05). But no significant differences were found according to activities that they choose in their leisure time.